Improving Students’ Cognitive and Affective Domains Students through Fostering Teacher Development - Kurniati Kurniati; Nurdin Nurdin; Nurasmawati Nurasmawati (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2020)
The aim of this paper is to discusses the practice of cousin marriage in the community of Kalola Village, Pasangkayu Regency, West Sulawesi. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using grounded theory approach. The results showed that the foster teacher pattern applied in MAN Insan Cendekia Palu City was a form of activity and guidance that was relative and consistent, and a series of active efforts that made a large contribution to students, in improving intellectual / academic aspects as well as good attitudes. . So that the foster teacher pattern is used as a series of activities as a vehicle to educate, nurture and socialize children in developing their abilities, in order to achieve family, community and school expectations. Some educators who serve as foster teachers apply authoritarian parenting with the aim that students are clear and do not repeat mistakes, and also authoritative parenting which provides more understanding and good guidance without heavy pressure and punishment.